RuvC protein resolves Holliday junctions via cleavage of the continuous (noncrossover) strands. - Bennett, R J (1995)
The RuvC protein of Escherichia coli resolves Holliday junctions during genetic recombination and the postreplicational repair of DNA damage. Using synthetic Holliday junctions that are constrained to adopt defined isomeric configurations, we show that resolution occurs by symmetric cleavage of the continuous (noncrossing) pair of DNA strands. This result contrasts with that observed with phage T4 endonuclease VII, which cleaves the pair of crossing strands. In the presence of RuvC, the pair of continuous strands (i.e., the target strands for cleavage) exhibit a hypersensitivity to hydroxyl radicals. These results indicate that the continuous strands are distorted within the RuvC/Holliday junction complex and that RuvC-mediated resolution events require protein-directed structural changes to the four-way junction.